THE DETERMINANT FRAUD PREVENTION OF QUALITY LOCAL GOVERNMENT’S FINANCIAL REPORT - Haryono Umar; Agustina Indriani; Rahima Br. Purba (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2019)
This study empirically aims to analyze the influence of government internal control system and internal monitoring on fraud prevention and its implications on the quality of local financial statements. The data in this study were 89 respondents of local government officials in the city of Bogor and Depok. The methodology using multiple linear regression analysis. The results of the study showed the internal control system positively affects fraud prevention, on the other hand the internal monitoring has no effect on fraud prevention. Fraud prevention has a positive effect on the quality of financial statements. While the government internal control system has a negative effect, the internal monitoring has a positive effect on the quality of local financial report. Government internal control system indirectly affects the quality of local financial statements through fraud prevention, whereas the internal control directly affects the quality of local financial statements through fraud prevention. The result also indicate the fraud prevention has a greater impact on the quality of local financial statements. Internal control system might be minimized fraud and possibility of error. It indicates that fraud prevention support the quality of local financial reporting.